The impact of external auditors on firms' financial restatements: a review of archival studies and implications for future research - Patrick Velte (Management Review Quarterly, 2022)
A systematic literature review includes 69 archival studies on the impact of external auditors on firms' financial restatements, based on principal agent theory. In more detail, we separate between auditor incentives and auditor competencies to supply a high audit quality. Financial restatements represent one of the most important proxies of audit quality in archival audit research, stressing an increased relevance in empirical research, business practice and regulatory initiatives. The review highlights that many studies on auditor incentives and competencies show inconclusive results on firms' financial restatements (e.g., fee and rotation studies). But there are indications that especially auditor expertise and audit firm size significantly decrease financial restatements. In discussing potential future research, we emphasize the need for a more detailed analysis of restatements proxies, controls for audit risk, inclusion of (corporate) governance mechanisms as possible moderators or mediators, and sustainability issues of the audit team.
Keywords: M41; M48; Q56; 650; Financial restatements; External auditor; Corporate governance; Restatements; Enforcement